Health Spending Growth at Zero Which Countries, Which Sectors Are Most Affected? - Morgan, David (OECD Health Working Papers, 2013)
Health spending slowed markedly or fell in many OECD countries recently after years of continuous growth, according to OECD Health Data 2012. As a result of the global economic crisis which began in 2008, a zero rate of growth in health expenditure was recorded on average in 2010, and preliminary estimates for 2011 suggest that low or negative growth in health spending continued in many of the countries for which data are available